Estimating red deer abundance in a wide range of management situations in Mediterranean habitats - Acevedo, P.; Ruiz-Fons, F.; Vicente, J.; Reyes-García, a R.; Alzaga, V.; Gortázar, C. (Journal of Zoology, 2008)
When human interventions interfere with the natural regulation of wildlife populations by favouring some species, overabundance can emerge. We evaluated different methods of estimating red deer abundance in a wide range of population densities from southern Spain. Distance sampling estimates were used as the reference method across 22 localities and were compared with two kilometric abundance indices (KAIs), four indices based on pellet group counts and two browsing indices (BWIs). The average red deer density estimated by distance sampling was 19.51 3.19 deer per 100 ha, showing a wide range across the study area (0.04–66.77). Distance sampling estimates correlated with the KAIs, pellet group-based index and the BWI. The agreement with distance sampling improved when groups were used instead of individuals in the KAIs, when the minimum pellet group size was ﬁxed at 20 pellets in the dropping counts, and when only highly palatable species were used in the BWI. Thus, several direct and indirect methods can estimate red deer abundance in Mediterranean habitats from Southern Spain with appropriate modiﬁcations.
Keywords: deer management; direct and indirect methods; Mediterranean area; overabundance; population abundance; red deer; ungulates

Estimating red deer abundance in a wide range of management situations in Mediterranean habitats - Acevedo, P; Ruiz-Fons, F; Vicente, J; Reyes-García, a. R; Alzaga, V; Gortázar, C (Journal of Zoology, 2008)
When human interventions interfere with the natural regulation of wildlife populations by favouring some species, overabundance can emerge. We evaluated different methods of estimating red deer abundance in a wide range of population densities from southern Spain. Distance sampling estimates were used as the reference method across 22 localities and were compared with two kilometric abundance indices (KAIs), four indices based on pellet group counts and two browsing indices (BWIs). The average red deer density estimated by distance sampling was 19.51 3.19 deer per 100 ha, showing a wide range across the study area (0.04–66.77). Distance sampling estimates correlated with the KAIs, pellet group-based index and the BWI. The agreement with distance sampling improved when groups were used instead of individuals in the KAIs, when the minimum pellet group size was ﬁxed at 20 pellets in the dropping counts, and when only highly palatable species were used in the BWI. Thus, several direct and indirect methods can estimate red deer abundance in Mediterranean habitats from Southern Spain with appropriate modiﬁcations.
Keywords: deer management; direct and indirect methods; Mediterranean area; overabundance; population abundance; red deer; ungulates

The dispersal of a dry-fruited shrub by red deer in a Mediterranean ecosystem - Malo, Juan E; Suárez, Francisco (Ecography, 1998)
Seed dispersal of dry-fruited shrubs has received little attention in Mediterranean areas despite their frequency in the vegetation and the consideration given to the dispersal of fleshy-fruited shrubs in the area. Red deer faeces has recently been found to contain large numbers of seeds from one of the most common shrubs of this group, gum cistus Cistus ladanifer, although its importance in the reproduction of the species is unknown. This study examines the role of the red deer as an effective disperser of C. ladanifer. For this purpose, we quantify i) the C. ladanifer seed content in red deer dung over a year, ii) the seed shadow generated by the red deer wish their faeces during the same period, and iii) the ability of the dung-borne seeds to germinate and establish as seedlings under field conditions within five years following excretion. The results reveal an extremely high seed Content of the species in red deer dung (up to 80.5 ± 41.9 germinable seeds g-1), which is virtually confined to the summer (July–August), when we estimate that a red deer defecates up to 24 000 seeds of the species per day. Furthermore, red deer mainly deposit gum cistus seeds amongst plant formations lacking the species: over the year, red deer excrete <2600 seeds m-2 in C. ladanifer-dominated scrub and 7400–8800 seeds m-2 in other plant formations. Under natural conditions, the dung-borne seeds have a more sniggered among-years germination pattern than free seeds in the soil. Though no seedling survived its first summer drought, the survival of seedlings sprouted from dung was significantly longer than that of control seedlings in the first and third years after deposition, and indistinguishable from it the second, fourth and fifth years. This is the first quantification of the importance of red deer to C. ladanifer dispersal and establishment, and suggests that endozoochory by mammalian herbivores can be very valuable for dry-fruited shrubs in the Mediterranean region.
Keywords: endozoochory; red deer; seed dispersal; seedling establishment (PG)

The dispersal of a dry-fruited shrub by red deer in a Mediterranean ecosystem - Malo, Juan E.; Suárez, Francisco (Ecography, 1998)
Seed dispersal of dry-fruited shrubs has received little attention in Mediterranean areas despite their frequency in the vegetation and the consideration given to the dispersal of fleshy-fruited shrubs in the area. Red deer faeces has recently been found to contain large numbers of seeds from one of the most common shrubs of this group, gum cistus Cistus ladanifer, although its importance in the reproduction of the species is unknown. This study examines the role of the red deer as an effective disperser of C. ladanifer. For this purpose, we quantify i) the C. ladanifer seed content in red deer dung over a year, ii) the seed shadow generated by the red deer wish their faeces during the same period, and iii) the ability of the dung-borne seeds to germinate and establish as seedlings under field conditions within five years following excretion. The results reveal an extremely high seed Content of the species in red deer dung (up to 80.5 ± 41.9 germinable seeds g-1), which is virtually confined to the summer (July–August), when we estimate that a red deer defecates up to 24 000 seeds of the species per day. Furthermore, red deer mainly deposit gum cistus seeds amongst plant formations lacking the species: over the year, red deer excrete <2600 seeds m-2 in C. ladanifer-dominated scrub and 7400–8800 seeds m-2 in other plant formations. Under natural conditions, the dung-borne seeds have a more sniggered among-years germination pattern than free seeds in the soil. Though no seedling survived its first summer drought, the survival of seedlings sprouted from dung was significantly longer than that of control seedlings in the first and third years after deposition, and indistinguishable from it the second, fourth and fifth years. This is the first quantification of the importance of red deer to C. ladanifer dispersal and establishment, and suggests that endozoochory by mammalian herbivores can be very valuable for dry-fruited shrubs in the Mediterranean region.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: endozoochory; red deer; seed dispersal; seedling establishment (PG)

Impact of feeding habits of Corsican red deer (Cervus elaphus corsicanus) on vegetation at Quenza Park in Corsica - Maillard, D; Casanova, J B; Gaillard, J M (MAMMALIA, 1995)
Following the translocation of Corsican red deer (Cervus elaphus corsicanus) in Quenza enclosures in 1985, we tried to assess the impact of red deer on woody mediterranean species. We found that sempervirent species with persistent leaves like Calytcotome villosa, Arbutus unedo, Quercus ilex and Cistus salviaefolius were eaten by deer all the year along. In fact, we identified three different categories of plant species according to the different levels of use by deer. A first groupe includes species highly and quickly consumed by deer like Calycotome villosa, Fraxinus ornus and Lonicera etrusca. These plants can even disappear when deer density becomes very high. A second group was composed of plant species red deer ate but searched for in a lesser extent like Arbutus unedo and Quercus ilex. Consumption of some of them showed a peak during summer (Rosa canina and Rubus sp.). in the last groupe, we pooled species weakly consumed by red deer, like Erica arborea and Cistus salviaefolius.
APS
Keywords: Arbutus unedo; Calytcotome villosa; Cervus elaphus corsicanus; Cistus salviaefolius; comsumption; Mediterranean; Quercus ilex; red deer

WINTER DIET OF RED DEER STAG (CERVUS-ELAPHUS L) AND ITS RELATIONSHIP TO MORPHOLOGY AND HABITAT IN CENTRAL SPAIN - ALVAREZ, G; MARTINEZ, T; MARTINEZ, E (FOLIA ZOOLOGICA, 1991)
The winter diet of red deer stags in a mediterranean environment of Central Spain is studied. Tree foliage and shrubs made up 95.5% of the diet, particularly Quercus rotundifolia (35.4%). Arbutus unedo (19.7%), Rosmarinus officinalis (9.4%), Phillyrea angustifolia (7%), Erica spp. and Cistus ladanifer. Herbaceous species formed 4% of the diet, mainly in a dry condition. There was a high similarity between the diets in the two periods studied, December and the end of January, with greater diversity in December. In January, the dominance of Quercus rotundifolia and Arbutus unedo increased. A relationship was detected of diet with body weight and antler growth. The largest animals consumed Arbutus unedo heavily, indicating a preference for forest understories with dense developed shrubs in mountain areas, while the smaller individuals associated with Erica umbellata, Phillyrea angustifolia and herbaceous species, had a wider diet niche and occupied less sheltered zones.
APS
Keywords: diet; Mediterranean; red deer; Spain